Reducing EFL Students’ Speaking Anxiety Through Vlog in English Education Study Program at Pattimura University - Meyer, Herman; Patty, Jusak (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
This study explores the potential of video blogs (vlogs) as an innovative intervention for mitigating speaking anxiety among English as a Foreign Language (EFL) students. Grounded in contemporary language anxiety and technology-enhanced learning theories, the research addresses a critical gap in understanding digital strategies for anxiety reduction. Employing a convergent mixed-methods design, the study investigated 39 first-semester students at Pattimura University's English Education Program. Data were collected through a questionnaire and in-depth semi-structured interviews. Quantitative analysis revealed a significant reduction in speaking anxiety, with a mean effectiveness score of 3.28 (SD = 0.48), particularly in performance enhancement (M = 3.40, SD = 0.50). Qualitative insights illuminated students' psychological transformations, demonstrating vlogs' potential to create supportive, self-directed learning environments. While context-specific, the findings contribute empirical evidence to the emerging field of technology-mediated language learning and offer promising strategies for addressing speaking anxiety in EFL contexts.